PERLINDUNGAN HUKUM BAGI PEMINJAM PADA FINTECH ONLINE - Ratnasih, Panca Galuh; Galuh, Catur (Yayasan Education and Social Center, 2024)
This study is to evaluate the legality of loan agreements. Online loans, as well as the potential for legal settlement associated with the Consumer Protection Act, OJK Regulation No. 77 of 2016, The method used is Qualitative normative legal method. Normative legal research is also called doctrinal research, where law is conceptualized as what is written in laws and regulations (law in books), and research on legal systematics can be carried out on certain written regulations or laws. The results of this study are Legal protection for users of applications on Fintech-based money lending services, there are regulations governing the implementation of this activity, business actors and fintech organizers in P2PL are required to pay attention to and implement the provisions of OJK Regulation Number 77 / POJK.07 / 2016 concerning Information Technology-Based Money Lending Services and Ministerial Regulation Number 20 of 2016 concerning Personal Data Protection in Electronic Systems Article 2 Paragraph (2), online loan organizers as business actors who carry out their business based on electronic systems are given the obligation to maintain the confidentiality of consumer data from the time it is obtained until the data is destroyed